PENGARUH GREEN ACCOUNTING, CORPORATE SOCIAL RESPONSIBILITY, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Asih, Fitri; Surachman, Ade Elza; Akbari, Safitri (Jurnal Riset Ilmu Akuntansi, 2026)
This research aims to analyze and explain the influence of green accounting, corporate social responsibility (CSR) and profitability on company value. The method used is a quantitative method. Using secondary data in the form of annual reports and company sustainability reports taken from the company's official website. The population used in this research is energy sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. The sampling method used in this research was a purposive sampling method with a total sample of 28 companies. The data analysis method used is multiple linear regression analysis using SPSS version 26 software. The results of this research show that green accounting (PROPER) has a negative and significant effect on company value (PBV), CSR (2021 standard GRI) has a positive and significant effect on company value (PBV), and profitability (ROA) has a positive and significant effect on company value (PBV).